Organ donation for transplants: knowledge and beliefs of residents from a country region of the Sao Paulo State - Faria , Jeovane G; Branco , Leda Maria; Miyazaki , Maria Cristina Oliveira Santos; Duarte , Priscila Silveira; Abbud-Filho , Mário (Brazilian Journal of Transplantation, 2007)
Organ shortage for transplantation is due to multiple factors, including people’s perception on such issue. Purpose: to inform and identify the opinion on organ donation and transplantation in residents of a country city of the state of Sao Paulo Methods: participants were asked to answer a questionnaire during the National Week of Brazilian Organs and Tissue Donation and Transplantation in a medium size country town. Results: 303 adults (52% women), 36% of them with college degree participated in the study. The majority (99%) had already heard on organ donation and transplantation. Although 92% of participants had a positive attitude towards organ donation, only 65% had informed their families about their wish to become a donor. Among those who agreed that organs from patients with cerebral death must be retrieved (90%), the percentage decreased when the donor was a relative (86%). 90% were against any type of reward for living donors and organ selling (79%). Age was considered a non-appropriate distribution criteria, 60% believed that children must have priority, and 75% thought that elder persons (<65 years) are eligible to the transplantation. The majority agreed that subgroups may receive organs, but the criteria to the waiting list must be respected: foreigners (73%), smokers (89%), obese (96%), prisoners and drug users (88%). 95% believed that living donor transplantation should be encouraged. Conclusion: results show attitudes of solidarity among the population, as well as an absence of discriminative attitudes towards the subpopulation of receptors. Comparison of data with the one found in a previous study conducted in the same location shows an increase towards a positive attitude concerning organ donation and transplantation.